T cell receptor expression in Sjögren's syndrome. Issue 10 (October 1991) - Zumla, A; Mathur, M; Stewart, J; Wilkinson, L; Isenberg, D
Abstract : T lymphocytes expressing the gamma/delta T cell receptor and B lymphocytes expressing CD5 are known to occur in expanded numbers in the peripheral blood of patients with primary Sjögren's syndrome. The cellular infiltrates for the surface phenotypic markers for alpha/beta and gamma/delta T cell receptors, CD4, CD8, CD45, and CD5 were examined in lip biopsy specimens from two patients with primary Sjögren's syndrome, six with secondary Sjögren's syndrome, and seven healthy controls. Most of the Sjögren's lip biopsy cellular infiltrates were T lymphocytes of the CD4 subset expressing the alpha/beta T cell receptor (mean 70%). The low prevalence of gamma/delta T cell receptor bearing cells in lip biopsy specimens is maintained in Sjögren's syndrome (mean 1.5%), and thus it seems unlikely that these lymphocytes bearing the gamma/delta T cell receptor have a major role in the immunopathology of Sjögren's syndrome. Over 70% of cells within the lesional infiltrate of primary and secondary Sjögren's syndrome expressed the CD5 and CD45 cell surface molecules.